Pluggable scheduling on an open-source based volunteer computing infrastructure - Dinis, G. (Institute of Electrical and Electronics Engineers Inc., 2014)
Nowadays, there are different types of computing infrastructures, like grids and volunteer communities, which have distinct needs and the preservation of energy or other resources is chief among them. This paper presents an attempt to incorporate pluggable scheduling into an existing open-source volunteer computing system named BOINC. Our efforts proved valid, as we managed to re-engineer BOINC to support different scheduling applications and interchange between them dynamically, with additional support for thermal-aware scheduling algorithms. Our aim is to start a path into what could be a collection of middleware tools with standardized integration to sensor systems to support distinct types of scheduling policies, without the need to recompile the server system. Â© 2014 IEEE.